EVALUATION OF ANTI PCL-1 ANTIBODY TITER IN A GROUP OF HEALTHY SCHOOL CHILDREN WHO LIVE IN LEPROSY ENDEMIC AREA FROM 2007–2010 - putri, rachmah diana; amiruddin, M. dali; tabri, farida; Adriaty, Dinar; Wahyuni, ratna; iswahyudi, iswahyudi; agusni, indropo; izumi, shinzo (Institute of Topical Disease Universitas Airlangga, 2010)
The